Perbedaan Pengetahuan Anemia dan Tablet Tambah Darah (TTD) Sebelum dan Sesudah Pendidikan Kesehatan Melalui Media Video dan Aplikasi Quizlet - Devita Sari; Gisely - Vionalita (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
The problem of anemia in adolescent girls will have a negative impact on decreased learning concentration and later pregnancy. Based on data of Indonesian Demographic and Health Survey (SDKI) in 2017, only 8% of young women answered correctly about the meaning of anemia and 23.4% answered they did not know about the cause of anemia. This study aims to determine differences in students knowledge about anemia and Tablets Added Blood (TTD) before and after health education through video media and Quizlet Applications. This research uses Quasi Experimental Design with Pretest-Posttest with Control Group Design. The sampling technique used Stratified Random Sampling for the experimental group of 30 respondents and the control group of 30 respondents. The results of the T-Dependent and T-Independent tests showed that there were differences in students knowledge about anemia and Tablets Added Blood (TTD) before and after health education through video media and Quizlet Applications, with a Pvalue 0,000. It is expected that Health Center and Schools can work together in providing health education through video media and the Quizlet Application by holding a Healthy Friday Program and the Health Center can employ specialized human resources educated in Information Technology (IT) to develop video media and online-based applications.